2022
DOI: 10.1016/j.scitotenv.2021.152790
|View full text |Cite
|
Sign up to set email alerts
|

Passively sensing SARS-CoV-2 RNA in public transit buses

Abstract: Affordably tracking the transmission of respiratory infectious diseases in urban transport infrastructures can inform individuals about potential exposure to diseases and guide public policymakers to prepare timely responses based on geographical transmission in different areas in the city. Towards that end, we designed and tested a method to detect SARS-CoV-2 RNA in the air filters of public buses, revealing that air filters could be used as passive fabric sensors for the detection of viral presence. We place… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
3
0
2
Order By: Relevance
“…Studies comparing surface and air samples collected in the same environment usually report significant differences in SARS-CoV-2 RNA prevalence between air and surface samples. Nevertheless, some authors report higher prevalence in surface swabs, 15 , 37 , 38 others in air samples 39 and others similar prevalence rates for both. 40 , 41 The reasons for this as well as for the overall variability could be (amongst others) related to differences in sampling and detection methods and the tools used, as well as to the intensity of public transport use, the actual COVID-19 incidence, properties of the currently circulating strains, environmental conditions and cleaning and disinfection procedures.…”
Section: Resultsmentioning
confidence: 87%
“…Studies comparing surface and air samples collected in the same environment usually report significant differences in SARS-CoV-2 RNA prevalence between air and surface samples. Nevertheless, some authors report higher prevalence in surface swabs, 15 , 37 , 38 others in air samples 39 and others similar prevalence rates for both. 40 , 41 The reasons for this as well as for the overall variability could be (amongst others) related to differences in sampling and detection methods and the tools used, as well as to the intensity of public transport use, the actual COVID-19 incidence, properties of the currently circulating strains, environmental conditions and cleaning and disinfection procedures.…”
Section: Resultsmentioning
confidence: 87%
“…Studies with volunteers have shown that SARS-CoV-2 RNA can be shed in aerosol particles in exhaled breath by people with a SARS-CoV-2 infection during respiratory activities such as breathing and talking, particularly during early stages of infection (Adenaiye et al, 2022; Ma et al, 2021; Tan et al, 2023). Previous studies in public transport have detected SARS-CoV-2 RNA in air samples taken on buses and from associated air conditioning filters (Hadei et al, 2021; Hoffman et al, 2022; Moreno et al, 2021). Others have not (Di Carlo et al, 2020), probably reflecting differences in sampling methodologies, prevalence of COVID-19 in the community, mitigation strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Data collection can inform policy decisions and refine modelling assumptions. Several studies have investigated the presence of SARS-CoV-2 RNA in public transport vehicles (Caggiano et al, 2021; Di Carlo et al, 2020; Hadei et al, 2021; Hoffman et al, 2022; Moreno et al, 2021). However, these studies have been carried out over short sampling timeframes.…”
Section: Introductionmentioning
confidence: 99%
“…La presencia de SARS-CoV-2 en el transporte público ha sido ampliamente estudiada a nivel mundial, centrándose en la detección de diferentes tipos de matrices. Hoffman et al (2022) detectaron 5/37 muestras positivas de filtros de aire en autobuses públicos en Seattle, Washington, EE. UU.…”
Section: Detección De Sars-cov-2 En Sistema De Drenajeunclassified
“…De acuerdo con las diferentes opiniones y percepciones sobre la seguridad o el riesgo de transmisión del SARS-CoV-2 en espacios cerrados como el transporte público, se han realizado varios estudios enfocados en la detección de ARN viral en diversas matrices ambientales como https://doi.org/10.15741/revbio.11.e1631 ISSN 2007-3380 aerosoles, sistemas de filtración de aire, superficies como pasamanos, botones y manijas de asientos en autobuses, estaciones de trenes y autobuses, detectando la presencia del virus en todas las muestras mencionadas (Caggiano et al, 2021;Singh et al, 2021;Hoffman et al, 2022;Gomes da Silva 2022). El desarrollo de este tipo de estudios contribuye a comprender y estimar el riesgo potencial de la presencia de pasajeros conscientes o inconscientes de ser positivos para COVID-19, factor de transmisión del SARS-CoV-2 en el transporte público; por esa razón, el propósito de este estudio fue detectar la presencia de ARN del SARS-CoV-2 en agua residual de tanques contenedores de sanitarios de autobuses nacionales e internacionales.…”
Section: Introductionunclassified